2014
DOI: 10.1186/2193-1801-3-506
|View full text |Cite
|
Sign up to set email alerts
|

Individual in vitro effects of ochratoxin A, deoxynivalenol and zearalenone on oxidative stress and acetylcholinesterase in lymphocytes of broiler chickens

Abstract: The contamination of consumer food and animal feed with toxigenic fungi has resulted in economic losses worldwide in animal industries. Mycotoxins are highly biologically reactive secondary metabolites and can inhibit protein synthesis and cell multiplication. Considering the cytotoxicity of mycotoxins, this experiment was performed to determine the in vitro influence of ochratoxin A, deoxynivalenol and zearalenone on lipid peroxidation in lymphocytes of broiler chickens at different concentrations. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Moreover, a previous report indicated that DON and other mycotoxins are activated by the hepatic cytochrome P 450 enzyme system to produce a highly reactive intermediates which subsequently binds to nucleophilic sites in DNA forming an adduct (Awad et al, 2012). Consequently, the formation of DON-DNA adducts is regarded as a critical step in the initiation of DON-induced hepatocarcinogenesis (Lautert et al, 2014). The results reported herein also revealed that treatment with DON induced DNA fragmentation in liver.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, a previous report indicated that DON and other mycotoxins are activated by the hepatic cytochrome P 450 enzyme system to produce a highly reactive intermediates which subsequently binds to nucleophilic sites in DNA forming an adduct (Awad et al, 2012). Consequently, the formation of DON-DNA adducts is regarded as a critical step in the initiation of DON-induced hepatocarcinogenesis (Lautert et al, 2014). The results reported herein also revealed that treatment with DON induced DNA fragmentation in liver.…”
Section: Discussionsupporting
confidence: 60%
“…Based on the previous studies, the mechanisms of OTA were explored [7,8,9,35,36,37]. Oxidative stress has an important role in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…OTA displays nephrotoxicity [4], hepatotoxicity [1], carcinogenicity [5], and neurotoxicity [6] in mammals. There are some studies that have revealed the mechanisms of OTA, such as, protein synthesis inhibition [7], lipid peroxidation [8], mitochondrial function inhibition [9], DNA methylation [10], miRNA regulation [11], the changes of enteric microorganism [12], renal cortex fibrosis, and epithelial-to-mesenchymal transition [13,14] etc. Some researchers also suggested that the toxicity is related to oxidative stress, and other researchers insist that DNA damage, including DNA adduct formation and DNA strand breaks, are responsible [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that alteration in AChE activity is one of the main causes for AD ( Talesa, 2001 ). Lautert et al (2014) showed that OTA induced acetylcholine esterase (AChE) activity which led to increased cellular oxidative stress levels. A member of the neurotrophin family, brain-derived neurotrophic factor (BDNF) directs neuronal cell survival, promotes growth and differentiation in the developing nervous system.…”
Section: Discussionmentioning
confidence: 99%